Millimeter wave channel modeling – present development and challenges in tropical areas - Budalal, Asma. Ali H.; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Abd Rahman, Tharek (IEEE, 2018)
Millimeter wave is the key enablers for modern wireless applications. The Utilization of millimeter wave technology becomes a key factor in solving the problem of bandwidth shortage. Millimeter wave leads to delivering much higher throughput, faster data rate, and capacity. However, it is still facing some technical challenges’. The main objective of this paper is to identify research challenges in the mm-wave channel and activities on modeling. A brief analysis of rain fading was presented based on simultaneously measurement of one-minute rain rate and its effects on a short experimental link of 38 GHz and rain fade is observed as high as 15 dB for 300 m path at about 125 mm/hr rain intensity. Hence rain attenuation at 0.001 % and 0.01% of outages must be considered for 38 GHz. The statistical spatial channel mode simulation software was utilized for an operating frequency of 38 GHz. To observe the received power and path loss, power delay profile (PDP) was generated. The omnidirectional and directional received power and path loss have been estimated using environmental parameters of Kuala Lumpur city which illustrates the theoretical performances of 5G in Malaysia. As the receiver moves from line-of-sight (LOS) to non-line-of-sight (NLOS) scenarios, a drop of 33.1 dB omnidirectional power is found.